Liquid Dessert : Cocktail Confections from Around the World - Paiement, Bryan (Book collections on Project MUSE., 2023)
"You're probably tired of asking the same old question, "What should we make for dessert?" The answer is simple-cocktails! In Liquid Dessert, professional bartender and mixologist Bryan Paiement invites you join him on a trip around the world to discover cocktails inspired by the best desserts on the planet. Liquid Dessert is not your average cocktail or dessert book but a glorious combination of the two. Traditional desserts, though delicious, can be heavy and overwhelming after a big meal. Or you may be wavering on whether or not to have another beverage or dessert-now it doesn't have to be one or the other! From cocktails-inspired favorites like Bananas Foster or Cannoli, whether you're a fan of rich, decadent chocolate or you have more of a citrusy-tart palette, the simple-to-follow recipes in Liquid Dessert have you covered, no matter your craving"--